Variations in the use of caesarean section: a Comparison between France and Australia. (13th November 2019) - Chevreul, K; Shand, A; Korb, D; LeRoux, E; Nassar, N; Sibony, O; Bisits, A; Alberti, C
Abstract: Background: There has been a rise in obstetric intervention during labour and birth including rates of caesarean section around the world. The rates of caesarean section are lower in France (20%) than Australia (34%). Both countries have universal health care systems. Australia has a well-established program of obstetric benchmarking and national data collection for comparing maternal and perinatal outcomes taking into account maternity units and maternal characteristics. Although the optimal caesarean section rate is not known, variation in caesarean section rates raise questions about what is driving variation in practice and whether the right care is being delivered. The World Health Organisation has recently released non-clinical recommendations aiming to reduce unnecessary caesarean sections, including that births are classified by Robson classification for easier comparison. Methods: We aim to compare rates of mode of birth in 2 tertiary hospitals- one in France and one in Australia using Robson classification. This project will investigate differences in patient casemix, and obstetric management that may lead to differences in outcome. In addition, we will try to explore differences in the health systems including clinical activity, induction rates, staffing (number, type (medical, nursing, midwifery)), and models of care. Outcomes: Caesarean section is one of the most common operations performed in hospitals. Important variations of surgical rates raise question regarding whether access to this procedure is optimized. Determining current practice and outcomes of women in two different settings will provide important data to inform hospital practice and further research. In addition, this research may inform national guidelines about indications for caesarean section.